A report on the Lemko Association and the Carpathian Institute of the USA in 2017 - Best, Paul J. (Zielona Góra: Oficyna Wydawnicza Uniwersytetu Zielonogórskiego)
This paper reports on the recent revival of the Lemko Association (Lemko Soyuz) in North America, under the auspices of the Carpathian Institute, a US federal and Connecticut state recognized tax-exempt, non-profit, non-political, non-sectarian educational corporation. The Lemko Association, founded in 1929, had become essentially defunct by the end of 2009. Beginning in 2010, however, in a new location and new legal status it has been revived, publishing a quarterly, "Karpatska Rus", books, pamphlets and flags and arranging for lectures.
Keywords: Lemko Association; Carpathian Institute; Lemko; United States of America